The effects of catalysts in biodiesel production: a review - Atadashi, I.M.; Aroua, M.K.; Abdul Raman, Abdul Aziz; Sulaiman, N.M.N. (Elsevier, 2013)
Biodiesel fuel has shown great promise as an alternative to petro-diesel fuel. Biodiesel production is widely conducted through transesterification reaction, catalyzed by homogeneous catalysts or heterogeneous catalysts. The most notable catalyst used in producing biodiesel is the homogeneous alkaline catalyst such as NaOH, KOH, CH 3ONa and CH 3OK. The choice of these catalysts is due to their higher kinetic reaction rates. However because of high cost of refined feedstocks and difficulties associated with use of homogeneous alkaline catalysts to transesterify low quality feedstocks for biodiesel production, development of various heterogeneous catalysts are now on the increase. Development of heterogeneous catalyst such as solid and enzymes catalysts could overcome most of the problems associated with homogeneous catalysts. Therefore this study critically analyzes the effects of different catalysts used for producing biodiesel using findings available in the open literature. Also, this critical review could allow identification of research areas to explore and improve the catalysts performance commonly employed in producing biodiesel fuel. Â© 2012 The Korean Society of Industrial and Engineering Chemistry.